Incidence of Peroneal Nerve Injury due to Corrective Osteotomy: Systematic Review and Meta-Analysis - Selawijaya, Yusuf (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Introduction: Peroneal nerve injury is one of the complications of corrective osteotomy, a procedure to repair deformities of the bone and joint. We were determined to find incidence of peroneal nerve injury among patients underwent corrective osteotomy. Methods: We conducted a systematic review and meta-analysis based on the PRISMA statement. Searching was carried out in several databases. Included studies after thorough screening were appraised using the JBI critical appraisal tools. Studies characteristics and results were extracted. Quantitative analysis was carried out to find the prevalence alongside the 95% confidence interval. Results: We found 6 studies involving 788 subjects. We found that peroneal nerve injury occurred in 7.30% (95% CI = 1.34% – 17.47%) of corrective osteotomy cases. Two studies reported no injury done with mean angle repair of 9.9 ± 1.8 and 3.7 ± 1.2 degrees. There were variations of recommendations on osteotomy locations to reduce risk of peroneal nerve injury. Conclusion: Peroneal nerve injury was observed in 7.30% of patients underwent corrective osteotomy. Better management and consideration in doing osteotomy could reduce the risk of peroneal nerve injury, hence increasing outcome and prognosis of the patients.